Extracorporeal shockwave therapy shows time-dependent chondroprotective effects in osteoarthritis of the knee in rats - Wang, Ching-Jen; Sun, Yi-Chih; Wong, To; Hsu, Shan-Ling; Chou, Wen-Yi; Chang, Hsueh-Wen (The Journal of surgical research, 2012)
Recent studies reported that extracorporeal shockwave therapy (ESWT) has a chondroprotective effect on the initiation and regression of osteoarthritis of the knee in rats. However, the time course effects of ESWT in the osteoarthritic knee are not fully understood. The purpose of this study was to evaluate the effects of ESWT over time on osteoarthritis of the knee in rats. We used 72 8-week-old male Sprague-Dawley rats with body weights ranging from 245 to 265 g. We randomly divided the rats into three groups, with 24 rats in each group. The control group received neither surgery nor ESWT. The anterior cruciate ligament transected (ACLT) group underwent anterior cruciate ligament transection but received no ESWT. The ACLT plus ESWT group underwent ACL transection and received ESWT at 1 wk after surgery. The animals were killed at 2, 4, 8, and 12 wk, 6 rats from each group at each time course. Evaluation parameters included Mankin score, Safranin O stain, and collagen II for the articular cartilage; and vascular endothelial growth factor (VEGF), bone morphogenetic-2 (BMP-2), and osteocalcin for the subchondral bone using histopathological examination and immunohistochemical analysis. The ACLT group showed significant increases in Mankin score and Safranin O stain, and a decrease in collagen II in the articular cartilage, and significant decreases in VEGF, BMP-2, and osteocalcin in the subchondral bone compared with the control (P < .05). The ACLT + ESWT group showed significant decreases in Mankin score and Safranin O stain and an increase in collagen II in the articular cartilage, and significant increases in VEGF, BMP-2, and osteocalcin in the subchondral bone compared with the control group. The changes in the ACLT + ESWT group appeared to correlate with the time courses of treatment; the most beneficial effects were noticed 4 weeks after ESWT. Extracorporeal shockwave therapy is effective in preventing osteoarthritis of the knee in rats. The beneficial effects of ESWT appear to be time-dependent beginning at 4 weeks after treatment.